The Role of Natural Products on Diabetes Mellitus Treatment: A Systematic Review of Randomized Controlled Trials - Lucía Vivó-Barrachina; María José Rojas-Chacón; Rocío Navarro-Salazar; Victoria Belda-Sanchis; Javier Pérez-Murillo; Alicia Peiró-Puig; Mariana Herran-González; Marcelino Pérez-Bermejo (MDPI AG, 2022)
The present study was carried out to relate the role of natural products in the metabolism of an increasingly prevalent disease, type 2 diabetes mellitus. At present, in addition to the pharmacological resources, an attempt is being made to treat diabetes mellitus with natural products. We carried out a systematic review of studies focusing on the role of natural products on diabetes mellitus treatment. The bibliographic search was done through Medline (Pubmed) and Web of Science. From 193 records, the title and summary of each were examined according to the criteria and whether they met the selection criteria. A total of 15 articles were included; after reviewing the literature, it is apparent that the concept of natural products is ambiguous as no clear boundary has been established between what is natural and what is synthetic, therefore we feel that a more explicit definition of the concept of "natural product" is needed. Gut microbiota is a promising therapeutic target in the treatment of diabetes. Therefore, it would be necessary to work on the relationship between the microbiome and the benefits in the treatment of diabetes mellitus. Treatment based solely on these natural products is not currently recommended as more studies are needed.